Probing signals with ZACZ for GPRonboard of unmanned aerial vehicle - Roman N. Ipanov; Aleksey A. Komarov (Institute of Advanced Engineering and Science, 2021)
Modern ground penetrating radars (GPR), designed to determine the thickness of ice or search for the occurrence of aquifers in arid regions of the Earth, are installed either on helicopters or on the earth's surface. The use of a helicopter is economically expensive, and the installation of GPRs on the earth's surface is of a local nature. Modern GPRs mainly use video pulse probing signals and probing signals with linear frequency modulation. These signals have correlation noise, which makes it difficult to obtain a high-quality radar image. In this work, we propose to use a signal with a zero autocorrelation zone (ZACZ) as a probing signal for GPR installed on an unmanned aerial vehicle. In work, a polyphase probing signal with a ZACZ is synthesized and a comparative analysis of the correlation characteristics of the synthesized signal with the optimal phase-code shift keyed signal is carried out.